Hubungan Status Gizi, Persen Lemak Tubuh, dan Kadar Hemoglobin Terhadap Kualitas VO2 Maks Siswa Sekolah Sepak Bola Sport Supaya Sehat Semarang - Bimantara, Gama; Hardiansyah, Angga; Darmu’in, - (Universitas Muhammadiyah Semarang, 2023)
Background: Have a good nutritional status, ideal body fat percentage and normal hemoglobin levels are needed for maintain physical endurance, physical fitness and help to improve the performance of football athletes. When the nutritional status and body fat levels are not ideal, it will interfere athlete mobility. Low hemoglobin levels could disrupt the metabolism of energy that can make an athlete have downgrade quality. Purpose: Know the relationship of nutritional status, body fat percentage, and hemoglobinlevels on the quality of VO2 max student levels from Sport Supaya Sehat (SSS) football school Semarang. Methods: This research was conducted with a cross sectional design at Sport Supaya Sehat (SSS) football school Semarang. All population is a sample which is has 56 respondent. Themeasured data are nutritional status was assessed with body mass index by age, body fat percentage was assessed using Bioelectrical Impedance Analysis, hemoglobin levels was measured using Easytouch GCHb tools and cardiorespiratory endurance was assessed using Yo-Yo test method. Bivariate analysis used Gamma test. Result: The majority characteristics of respondents are have a good nutritional status(69,6%), moderate fat percentages(62,5%), normal hemoglobin levels(71,4%), and good quality of VO2 max levels(55,4%). Bivariate analitical result are nutritional status and body fat percentage has no significant relationship with VO2 max quality levels (p>0,05). Hemoglobin level has significant relationship with VO2 max quality levels (p<0,05). Conclusion: There is a significant relationship between hemoglobin levels with VO2 max quality levels.Key words: Nutritional status; body fat percentage; hemoglobin; VO2 max